Desenvolvimento de arranjo esférico de microfones e sua aplicação na medição da resposta espacial de salas - Deboni, Guilherme Corrêa (2020)
This thesis aims at measuring room impulse responses with a spherical microphone array. The array consists of 32 microphones distributed throughout the surface of a rigid sphere. The text brings the methodology used to design the spherical microphone array and its application in real case scenarios. Impulsive responses were simulated for some room configurations and measured in two real rooms. The signals acquired with the spherical array were processed with conventional beamforming an energy analysis of directional impulsive responses. The results show the array’s capacity to detect the sound sources and wall reflections in both simulated and measured environments. An energy analysis shows, through a spherical grid, what are the directions of the remaining energy in the room.